2022
DOI: 10.3390/tomography8010030
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Gradient Characteristics Warrants Model-Based Correction of Diffusion Weighting Bias

Abstract: The study aims to test the long-term stability of gradient characteristics for model-based correction of diffusion weighting (DW) bias in an apparent diffusion coefficient (ADC) for multisite imaging trials. Single spin echo (SSE) DWI of a long-tube ice-water phantom was acquired quarterly on six MR scanners over two years for individual diffusion gradient channels, along with B0 mapping, as a function of right-left (RL) and superior-inferior (SI) offsets from the isocenter. Additional double spin-echo (DSE) D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Multiple studies of bias/repeatability/reproducibility of ADC on clinical MRIs using DWI phantoms are available [ 22 , 23 , 24 , 25 , 26 ]. Spatial nonuniformity of ADC as a function of x–y offset, as well as z-location on clinical scanners, has been studied using specialized phantoms and procedures [ 43 , 44 , 45 , 46 ] within FOVs much larger than typical for preclinical scanners. In our study, we limited ADC nonuniformity measurements to small offsets (±25 mm) relevant for mouse DWI along the bore axis (z-direction), since this typically is the most nonuniform direction on clinical scanners, as predicted by horizontal bore gradient coil design specifications [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies of bias/repeatability/reproducibility of ADC on clinical MRIs using DWI phantoms are available [ 22 , 23 , 24 , 25 , 26 ]. Spatial nonuniformity of ADC as a function of x–y offset, as well as z-location on clinical scanners, has been studied using specialized phantoms and procedures [ 43 , 44 , 45 , 46 ] within FOVs much larger than typical for preclinical scanners. In our study, we limited ADC nonuniformity measurements to small offsets (±25 mm) relevant for mouse DWI along the bore axis (z-direction), since this typically is the most nonuniform direction on clinical scanners, as predicted by horizontal bore gradient coil design specifications [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…62 Together with our observations with b =1000 and 2000 (s/mm 2 ), it could be speculated that some interactions (or cross-terms) between imaging and diffusion sensitizing gradients might have played an important role in modulating mean diffusivity. 63 Nonetheless, more research is warranted to further clarify this unresolved finding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in previous studies . 14,17,30 Therefore, this bias should be considered and corrected prior to the analysis of clinical DWI. Our findings also confirmed that GNL affected the ADC measurements for the right liver lobe, kidneys, spleen, and paraspinal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The gradient systems are designed to be as linear as possible but have in practice an unavoidable nonlinear component, 12 which causes spatial-dependent nonuniformity bias in the ADC measurements. [13][14][15][16][17][18][19][20][21] Several studies have used ambient temperature DWI phantom idea with isocenter ADC normalization to characterize spatial ADC bias caused by gradient nonlinearity (GNL). 13,22,23 Therefore, correction algorithms have been introduced in the new generation MRI systems to calibrate the images and overcome the GNLrelated image distortions.…”
mentioning
confidence: 99%
See 1 more Smart Citation